Analysis of Goods and Services Procurement System at The Central Statistical Agency of East Nusa Tenggara Province - Reinamah, Clara Margilina (Bisman - Jurnal Bisnis & Manajemen, 2022)
The research was intended to identify the system of goods and services procurement at the Central Statistical Agency of East Nusa Tenggara Province. It is a qualitative descriptive study. Data collection uses methods of interviews, document studies and literature studies. The type of data used was qualitative that resulted from interview. The data-analysis technique used is qualitative descriptive, which describes a statistical central system for supplying goods and services. Research shows that the system for procurement of goods and services to the central statistics of East Nusa Tenggara Province, based on President Rule Number 16, 2018: (1) Efficient (2) Effective (3) Transparent (4) Open (5) Competitive (6) Fair/non-discrimination (7) Accountable. Identify needs correctly to ensure that the procurement of goods/services is in accordance with the needs of BPS NTT Province and HPS (Self Estimated Price) compiled based on the expertise of reliable sources of information.